Wear it well : reclaim your closet and rediscover the joy of getting dressed - Bornstein, Allison (Chronicle Prism, 2023)
"Celebrity fashion stylist Allison Bornstein's Three Word Method and AB Closet Editing System will inspire you to find your personal style, curate your closet, overcome common wardrobe struggles, and use fashion as the ultimate tool for self-discovery and self-care"--